2009
DOI: 10.1590/s0103-84782009005000086
|View full text |Cite
|
Sign up to set email alerts
|

Tilletia barclayana: biologia e manejo em arroz irrigado

Abstract: ITilletia barclayana: biologia e manejo em arroz irrigado

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Rice kernel smut incidence is affected by rice cultivars (Slaton et al, 2007), seeding rate or their interaction. However, its has been proven that this disease is nor affected by air temperature nor by precipitation (Biswas, 2003) and Zemolin et al, (2009) reported the rice kernel smut (T. barclayana), which is considered as a secondary disease, lately has been growing in importance due to its high infestation levels and effects in rice yield.…”
Section: Introductionmentioning
confidence: 99%
“…Rice kernel smut incidence is affected by rice cultivars (Slaton et al, 2007), seeding rate or their interaction. However, its has been proven that this disease is nor affected by air temperature nor by precipitation (Biswas, 2003) and Zemolin et al, (2009) reported the rice kernel smut (T. barclayana), which is considered as a secondary disease, lately has been growing in importance due to its high infestation levels and effects in rice yield.…”
Section: Introductionmentioning
confidence: 99%